Pulmonary embolism following urological non-oncological surgery: The clinical features, management, and long-term follow-up outcome from a tertiary hospital of China - Wu, Ziqiang; Liu, Xuesong; Zhu, Quan; Li, Haozhen; Li, Kaixuan; Wang, Guilin; Tang, Zhengyan; Wang, Zhao (Frontiers in Surgery, 2022)
Objective To evaluate the clinical features, treatment, and outcomes of pulmonary embolism (PE) after urological non-oncological surgery in a tertiary hospital of China. Methods A total of eight patients who suffered from PE after urological non-oncological surgery from 2016 to 2019 were recruited to the study. Clinical data such as symptoms, vital signs, electrocardiogram, echocardiography, and computed tomographic pulmonary arteriography (CTPA) were reviewed. In addition, the management and long-term follow-up outcome of PE were reported. Pulmonary Embolism Quality of Life (PEmb-QoL) questionnaire was applied for five patients to evaluate health-related quality of life after PE. Results All patients survived during their hospitalization, and five patients were contacted during follow-up. Five of the eight patients were anticoagulated regularly until the re-examination results of CTPA and lower extremities ultrasound were normal. The period of anticoagulant sustained at least one month for each patient. The long-term follow-up outcomes showed that PE had little impact on the patients' quality of life. Conclusions The study demonstrated that the prognosis of PE patients was not as terrible as feared when treated immediately in the ward. Early diagnosis and treatment of PE is vital for prognosis. However, further verifications based on the results of large studies are still needed.